Evaluation of the Impact of Implementing Electronic Prescription in an Oncology Referral Hospital in Recife, Brazil - Falcão, Diana Carla Gouveia; Soares, Ana Lara Vieira; Araujo-Junior, Hermes Castro de; Souza-Filho, José Kilderlan Nascimento de; Medeiros, Natália Moura Farias de; Mota, Paulo Victor Brasileiro; Madeira-Neto, Rodolfo Basílio; Maia, Tiago Costa; Pereira, Marcio Roberto Pinho; Medeiros, Maria Angelina Silva (Brazilian Journal of Oncology, 2025)
Introduction The occurrence of errors in the prescription of antineoplastic oncological drugs constitutes a serious public health problem, directly affecting patient safety. In Brazil, the Protocol for the Safety in Prescription, Use, and Administration of Medications, established in 2013, aims to improve care related to medication use in healthcare facilities. This study aims to evaluate the prescription profiles of patients undergoing antineoplastic chemotherapy treatment admitted to the Pernambuco Cancer Hospital before and after the implementation of electronic prescription.Materials and Methods The present cross-sectional study was conducted by analyzing manual and electronic prescriptions collected from the clinical oncology ward of the Pernambuco Cancer Hospital during the periods from March to May 2016 and from June to August 2016, respectively. The data collected were extracted into a specific instrument, previously adapted for the study, containing information related to patients, prescribers, and medications. Descriptive statistics were used for data analysis.Results Among the 694 prescriptions analyzed, prescription errors were found in at least one item, with the omission of the patients' sex and bed number being the most common findings.Conclusion All of the prescriptions analyzed, both pre- and postcomputer standardization, contained errors in their completion. With the standardized prescriptions, a significant impact was observed in reducing these rates, especially regarding omission of items and information.
Keywords: prescriptions; medication errors; antineoplastic agents